Manifestations of Early Christianity in Rural Areas of Toletum and its Vicinity: Issues about Sarcophagi and Paleochristian Funeral Spaces - Tsiolis, Vasilis (ARYS. Antigüedad: Religiones y Sociedades, 2021)
The few written sources and poor archaeological evidence available on the earliest manifestations of Christianity in the area of the current province of Toledo (Spain) date from the beginning of the 4th century and suggest the existence, at this time, of a consolidated episcopal authority in Toletum and a growing connection of some wealthy landowners with the Christian religion. Taking into account the current state of research and with the aim of contributing to the debate on the implantation of this religion in the rural environment of Toledo and its bordering territories, during the earliest period to which written and material sources give access, in this paper are discussed questions raised both by the available documentation and some previous scholars’ hypotheses.